Architecture and Energy: Performance and style - Braham, William W.; Willis, Daniel (Routledge, 2013)
Does energy consumption influence architectural style? Should more energy-efficient buildings look different? Can that "look" be used to explain or enhance their performance? Architecture and Energy provides architects and architectural theorists with more durable arguments for environmental design decisions, arguments addressing three different scales or aspects of contemporary construction. By drawing together essays from the leading experts in the field, this book engages with crucial issues in sustainable design, such as: The larger role of energy in forming the cultural and economic systems in which architecture is conceived, constructed, and evaluated The different measures and meanings of energy "performance" and how those measures are realized in buildings The specific ways in which energy use translates into the visible aspects of architectural style. Drawing on research from the UK, US, Europe, and Asia the book outlines the problems surrounding energy and architecture and provides the reader with a considered overview of this important topic.